Analisis Kromatografi Lapis Tipis (KLT) dan Aktivitas Antihiperurisemia Ekstrak Rebung Schizostachyum brachycladum Kurz (Kurz) pada Mencit Putih Jantan - Yohannes Alen; Fitria Lavita Agresa; Yori Yuliandra (Jurnal Sains Farmasi & Klinis, 2017)
Thin-layer chromatography (TLC) analysis of bamboo shoot extract (Schizostachyum brachycladum) and its antihyperuricemic activity evaluation on male mice have been conducted. The extraction was processed by the maceration method, while the determination of the compound was carried out by using various color reagents of TLC plate. To evaluate the antihyperuricemic activity of the extract, a total of 25 male mice were hyperuricemic-induced with daily chicken liver homogenates along with extract suspension at doses of 25, 50 and 100 mg/kg, allopurinol 10 mg/kg, and control group. Another group consisted of 5 mice was treated as the normal group. Serum uric acid level of mice was measured by using the spectrophotometer at the 8th day and analyzed with one-way ANOVA. The TLC analysis showed that the extract contained phenolic compounds and triterpenoids. The measurement of serum uric acid levels revealed that the extract at doses of 25, 50 and 100 mg/kg significantly decreased the uric acid levels of male white mice as compared with control (p<0.05). However, all doses did not show any significant difference in reducing the uric acid level (p>0.05). The study concluded that bamboo shoot extract exhibited antihyperuricemic activity. The effect was seen even at the lowest dose evaluated.